Effect of consumption of Perna Viridis on hematological parameters in rats / Nur Syazwani Ahmad Fadzil and Mazura Bahari - Ahmad Fadzil, Nur Syazwani; Bahari, Mazura (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Perna viridis has been used as a traditional remedy for a variety of diseases for centuries. It also contains nutrients such as calcium, potassium, zinc, iron, phosphorus and copper that may help to increase hematological parameters a good source of minerals Thus, Perna viridis has the potential to be used to boost blood parameters. This study aimed to quantify the amount of protein and to determine the effect of Perna viridis on hematological parameters in rats. The sample was processed through the freeze-drying process and the amount of protein was determined using the Bradford assay. Eighteen rats were randomly divided into 3 groups: control (normal diet), low dose (7.0 mg/ml protein / kg) and high dose (52.0 mg/ml protein / kg. Treatment groups were given each dose orally for three weeks. The control group was given distilled water. All groups were kept under similar conditions. Each rat's blood was taken via cardiac puncture and analyzed using the CELL- DYN Abbott Emerald analyser for a variety of hematological markers. The results revealed that the protein content of the extract was 5.5 mg/ml. Hemoglobin concentration showed an increase in the mean for the high dose group and low dose group compared to the control group. As for platelet count, there is a significant increase in the low dose group (p<0.05) compared to the high dose group. It has been proven that Perna viridis has the ability to increase the platelet count at low doses. It would be a promising source of protein and could be recommended as an effective alternative way to increase platelet transfusion in more natural ways.